Principles of laboratory instruments - Schoeff, Larry E.; Williams, Robert H. ([S.l.] : Mosby-Year Book, 1993)
Intended for clinical laboratory personnel, pathologists, biochemists and cytologists, this basic textbook covers the use of instruments in the clinical laboratory. The concepts of electricity and electronic components and principles of instrumentation and automation in the laboratory are covered.
Keywords: laboratory instrument